Avaliação de cursos de graduação na Universidade Federal da Paraíba como instrumento para melhoria do ensino - Willat, Maria Alexandra (2018)
The promotion of the improvement of the quality of higher education is one of the purposes of the National System of Evaluation of Higher Education. Based on this premise, the present research aimed to analyze how the Graduation Courses Evaluation (ACG) is used as an instrument to make decisions for the improvement of undergraduate education in the UFPB. We opted for an exploratory research supported by documentary and bibliographical research and field research, conducted by semi-structured interviews. The time cut is from the management that began in 2012 until 2017, with the reappointment of the current Rector in 2016. The data were analyzed from the conceptual dimension of evaluation, of the institutional dimension; and the political dimension. The results of the analysis of the collected data revealed that the majority of the interviewees understood that the results from the ACG are a source of information about the strengths and weaknesses of the courses and should be used for policy making and institutional decision making by academic and institutional managers. It was still possible to identify that the current sector responsible for the improvement of undergraduate education needs to be regulated and establish its identity in order to become a strategic sector for the improvement of undergraduate education in the UFPB.